Lithium concentration and recurrence risk during maintenance treatment of bipolar disorder: Multicenter cohort and meta‐analysis - Hsu, Chih‐Wei; Carvalho, Andre F.; Tsai, Shang‐Ying; Wang, Liang‐Jen; Tseng, Ping‐Tao; Lin, Pao‐Yen; Tu, Yu‐Kang; Vieta, Eduard; Solmi, Marco; Hung, Chi‐Fa; Kao, Hung‐Yu (Acta psychiatrica Scandinavica, 2021)
Objective To compare differences in efficacy during maintenance treatment for bipolar disorder (BD) according to lithium serum levels. A multicenter retrospective cohort study and a dose‐response meta‐analysis were conducted. Methods The cohort study was conducted in Taiwan from 2001 to 2019 to identify patients with euthymic BD according to different serum levels (<0.4, 0.4–0.8, and 0.8–1.2 mmol/L). We adopted adjusted hazard ratios (aHRs) with 95% confidence intervals (CIs) for time to the recurrence of mood episodes having the <0.4 mmol/L group as the reference group. Moreover, we systematically searched for related articles in major databases before January 31, 2021 (PROSPERO: CRD42021235812). We used random‐effects modeling to estimate the dose‐response relationships between lithium serum levels and recurrence of mood episodes, which were depicted as odds ratios (ORs) with 95% CIs. Results A total of 1406 participants (cohort: 466; meta‐analysis: 940) were included. In the cohort study, the 0.4–0.8 mmol/L group was associated with a significantly lower risk of recurrences (aHR: 0.75), while the 0.8–1.2 mmol/L group had a lower risk without statistical significance (aHR: 0.77). The dose‐response meta‐analysis showed that with the increase in lithium serum levels, the risk decreased (linear model OR: 0.85, for every 0.1 mmol/L increase; non‐linear model OR: 1.00 at 0.0 mmol/L, 0.42 at 0.4 mmol/L, and 0.27 at 0.8 mmol/L). Conclusion Although confounding by indication cannot be excluded, the combined results suggest a significant preventative effect on the recurrence of major affective episodes among those with serum levels of 0.4–0.8 mmol/L.